2001
DOI: 10.1046/j.1528-1157.2001.41900.x
|View full text |Cite
|
Sign up to set email alerts
|

Typical and Atypical Perfusion Patterns in Periictal SPECT of Patients with Unilateral Temporal Lobe Epilepsy

Abstract: Summary:Purpose: To characterize perfusion patterns of periictal single-photon emission tomography (SPECT) in patients with unilateral temporal lobe epilepsy (TLE) and to determine their relationship to the epileptogenic zone (EZ).Methods: We studied periictal SPECT scans of 53 patients after anterior mesial temporal lobectomy who had good seizure outcome after surgery. Ictal SPECT scans were performed during video-EEG monitoring. Typical SPECT patterns consisted of ipsilateral ictal hyperperfusion or ipsilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 29 publications
0
26
1
5
Order By: Relevance
“…Several studies have demonstrated that the CBF can be used to characterize tumor microvascularity, including gliomas (24) and lymphomas (25). In a study of temporal lobe epilepsy, patterns of cerebral hypo-and hyperperfusion were found (26). For the clinical routine, a stable modality for whole-brain perfusion imaging is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that the CBF can be used to characterize tumor microvascularity, including gliomas (24) and lymphomas (25). In a study of temporal lobe epilepsy, patterns of cerebral hypo-and hyperperfusion were found (26). For the clinical routine, a stable modality for whole-brain perfusion imaging is needed.…”
Section: Discussionmentioning
confidence: 99%
“…SPECT enable the noninvasive examination of epileptogenic tissue and its functional status and the monitoring of the effect of treatment on regional and global function [23]. Epilepsy surgery is recommended for patients who do not benefit from Antiepileptic drugs (AEDs) treatment and, in that sense, intractability is an essential requirement to indicate the procedure [24]. Only 25 to 45% of the people with epilepsy are seizure free after 12 months with AED treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The presurgical workup commonly includes Magnetic Resonance Imaging (MRI), long-term Video-Electroencephalographic monitoring (VEEG), neuropsychological evaluation and functional neuroimaging with Single Photon Emission Tomography (SPECT). Periictal SPECT is widely available and highly sensitive to determine EZ location [24]. In those patients presenting extra-temporal epilepsy, non-localizing and non-lateralizing ictal and periictal EEG, normal MRI findings or multiple cerebral lesions, the ictal SPECT assumes an exploratory rather than purely complementary role [1,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algumas vezes, nos estudos pós-ictais precoces (com injeção do radiofármaco de um até cinco minutos após o término da crise) ocorre o chamado "desvio pós-crítico" (post-ictal switch), que consiste na combinação de hipoperfusão medial com hiperperfusão lateral, e constitui achado confiável na lateralização do foco 3,6,12,13 . Estudos sugerem a ocorrência de padrões típicos e atípicos de perfusão evidenciados pelo SPECT, mesmo ictal, que também podem contribuir para a lateralização do foco epileptogênico 14 . A eplepsia do lobo temporal (ELT) é a síndrome epiléptica mais comum dos adultos, sendo responsável por cerca de 40% dos casos, e em mais de 50% apresenta refratariedade medicamentosa 5,[15][16][17][18][19] .…”
unclassified